A Cu with continuously tunable plasmon resonance absorption 2-x S nanoparticle preparation method

By using reducing Ce3+ ions to assist in reducing Cu2+ ions under low temperature conditions, Cu2-xS nanoparticles with adjustable copper vacancy content are prepared, which solves the safety and complexity problems when preparing Cu2-xS nanoparticles in the prior art, and realizes the continuous adjustability of plasma resonance absorption in the NIR-II biological window, which is suitable for a variety of biomedical applications.

CN119118185BActive Publication Date: 2025-03-25HANGZHOU INST FOR ADVANCED STUDY UCAS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411612349.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The prior art faces safety problems of high temperature heating, the use of toxic solvents, the complexity of nanoparticles surface modification, and cumbersome collection and purification steps, etc., which affects large-scale, controllable and repeatable synthesis and its application in the field of biomedical science.

Method used

Cu2-xS nanoparticles with adjustable copper vacancy content can be prepared by using reducing Ce3+ ions in an alkaline environment as an electron donor under a low temperature 37°C water bath, thereby achieving continuous adjustable plasma resonance absorption in the NIR-II biological window.

Benefits of technology

This method has the advantages of gentle and controllable process and strong repeatability. The nanoparticles produced have the characteristics of good dispersion and uniform size distribution. The plasma resonance absorption is continuously adjustable in the NIR-II biological window. It is suitable for high-noise ratio photoacoustic imaging, high photothermal conversion efficiency, photothermal therapy and photothermal catalysis and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118185B_ABST
    Figure CN119118185B_ABST
Patent Text Reader

Abstract

The present invention provides a Cu with continuously adjustable plasma resonance absorption 2‑x S nanoparticle preparation method, the method uses albumin as a biomacromolecule ligand and Cu 2+ and S 2‑ ions as reaction precursors, using the reducing Ce 3+ As an auxiliary cation, NaOH was added to break the disulfide bonds in albumin to expose the nucleation sites, and the three-dimensional spatial conformation of albumin was used to limit the growth of nanoparticles. By adjusting the ratio of Cu and Ce elements, the plasma resonance absorption of ultra-small Cu nanoparticles with continuous adjustable properties was achieved. 2‑x The process of the present invention is simple, easy to control, low in cost and highly repeatable; the Cu 2‑x S nanoparticles have good dispersibility, a size distribution of 2‑3 nm, and continuously adjustable plasmon resonance absorption in the second near-infrared biological window.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano functional materials, and specifically relates to a Cu nanostructured material with continuously adjustable plasma resonance absorption. 2-x S nanoparticle preparation method. Background Art

[0002] Plasma nanomaterials are a type of nanomaterials with local surface plasmon resonance properties. Through interaction with incident light, under the mechanism of plasma-photon coupling, they can exhibit unique physicochemical effects such as plasma resonance optical absorption and efficient photothermal conversion, making them have extremely important application potential and value in biological fields such as photoacoustic imaging, photothermal therapy, photothermal catalysis, and photothermal controlled drug release.

[0003] Noble metal nanocrystals are a class of widely studied plasmonic nanomaterials, whose plasmon resonance absorption is mainly concentrated in the visible light region and the first near-infrared biological window (NIR-I, 650-950 nm). Non-stoichiometric copper sulfide (Cu 2-x S), as a semiconductor material, exhibits plasma resonance absorption in the second near-infrared biological window (NIR-II, 1000-1350 nm) due to its unique internal copper vacancy structure. Compared with visible light and NIR-I, NIR-II has deeper tissue penetration and lower photon scattering in biological tissues, and Cu 2-x Compared with precious metals, S has advantages such as good thermal stability and low price, which makes it have broader application prospects in the biological field. 2-x The tunability of S in the NIR-II biological window plasmon resonance optical absorption is an important prerequisite for meeting diverse usage needs, such as improving the signal-to-noise ratio of in vivo photoacoustic imaging and achieving photothermal effects with high photothermal conversion efficiency in vivo and in vitro. In addition, the realization of ultra-small Cu with a size of less than 5 nm 2-x The controllable preparation of S is crucial to promote the rapid renal clearance of nanoparticles in vivo, avoid the risk of long-term retention in the body, and ensure biosafety.

[0004] Solvothermal method and high temperature thermal decomposition method are the classic methods for preparing inorganic nanoparticles, which have achieved the ultra-small Cu 2-x However, these methods still face many challenges, such as the safety of high-temperature heating, the use of toxic solvents, the complexity of nanoparticle surface modification, and tedious collection and purification steps, which greatly affect the large-scale, controllable and reproducible synthesis and its wide application in the biomedical field. Therefore, the development of greener, more efficient and biocompatible preparation methods is of great significance to promote the development of Cu 2-xThe development of S nanomaterials in the biological field is of great significance. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a Cu nanostructured carbon nanotube having a continuously adjustable plasma resonance absorption in the NIR-II biological window. 2-x The method is an innovative method for preparing S nanoparticles, which has the advantages of mild and controllable process, strong repeatability, and the prepared nanoparticles have the characteristics of good dispersion and uniform size distribution.

[0006] The present invention cleverly utilizes the reducing Ce in an alkaline environment. 3+ ions act as electron donors to assist in the reduction of Cu 2 + ions, thereby preparing a non-stoichiometric Cu ion with adjustable copper vacancy content and continuously adjustable plasmon resonance absorption in the NIR-II biological window. 2-x S nanoparticles.

[0007] This is achieved specifically through the following technical solutions:

[0008] A Cu with continuously tunable plasmon resonance absorption 2-x The method for preparing S nanoparticles comprises the following steps:

[0009] (1) Dissolve albumin in ultrapure water (resistivity: 18.3 MΩ•cm) in a 37°C water bath.

[0010] (2) Under stirring, add copper chloride solution to the albumin solution of step (1), wherein the mass ratio of copper chloride to albumin is 0.05-0.08:1.

[0011] (3) Add cerium chloride solution to the mixed solution in step (2) under stirring, wherein the reducing Ce 3+ As a key auxiliary cation, it is used to regulate Cu 2-x The copper vacancy concentration of S nanoparticles and the molar ratio of cerium chloride to copper chloride are 0~0.05:1.

[0012] (4) Under stirring, add sodium hydroxide solution to the mixed solution of step (3), wherein the concentration of the sodium hydroxide solution is 40-60 mg / mL, and the mass ratio of sodium hydroxide to albumin is 0.08-0.1:1; quickly add the sodium hydroxide solution to break the disulfide bonds of the albumin to expose the nucleation sites, and stir the reaction for 3-5 min.

[0013] (5) Under stirring, add sodium sulfide solution to the mixed solution of step (4) at a concentration of 30-60 mg / mL, with the molar ratio of copper chloride to sodium sulfide being 1:2; quickly add the sodium sulfide solution to ensure rapid nucleation of the nanoparticles, and stir the reaction for 2 h.

[0014] (6) After stirring, the unreacted ions are first removed by dialysis, and then the possible agglomerates are further removed by low-speed centrifugation. The centrifugation speed is 5000-6000 rpm, and the centrifugation time is not less than 5 min. The supernatant is collected to contain ultra-small Cu 2-x The invention discloses a solution of S nanoparticles, wherein the nanoparticles in the solution have excellent dispersibility and uniform size distribution.

[0015] The size of the nanoparticles prepared by the above preparation method is 2~3 nm, and they have the advantages of uniform particle size distribution and good water solubility. In addition, the plasma resonance absorption of the prepared ultra-small nanoparticles is continuously adjustable in the second near-infrared region of 1000-1350 nm.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) The technical route of the present invention has the advantages of high controllability and repeatability, and the synthetic raw materials are cheap, safe and environmentally friendly, and easy to prepare in large quantities;

[0018] (2) The present invention cleverly utilizes the three-dimensional spatial conformation of the biomacromolecule albumin to limit the growth of nanoparticles, making it easy to controllably prepare ultra-small Cu 2-x S nanoparticles, which meet the needs of rapid renal metabolism in the body;

[0019] (3) The present invention is based on the preparation of Cu based on the biomacromolecule albumin 2-x S nanoparticles, without additional surface modification, have good aqueous solution dispersibility and excellent biocompatibility;

[0020] (4) The present invention can effectively adjust the Cu by adjusting the reaction ratio of copper and cerium. 2-x The plasma resonance characteristics of S enable its optical absorption to be continuously enhanced in the NIR-II biological window, and it exhibits excellent and stable photothermal conversion effect under NIR-II laser irradiation. It can be used in high signal-to-noise ratio photoacoustic imaging, high photothermal conversion efficiency, photothermal therapy, and photothermal catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the Cu prepared in the example 2-x Transmission electron microscopy image of S nanoparticles;

[0022] Figure 2The Cu-containing 2-x Hydration kinetics of S nanoparticles;

[0023] Figure 3 The Cu-containing 2-x Plasmon resonance absorption pattern of S nanoparticles;

[0024] Figure 4 The Cu-containing 2-x Plasmon resonance absorption pattern of S nanoparticles;

[0025] Figure 5 The Cu prepared in the embodiment with a Ce / Cu reaction ratio of 5% 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-x The photothermal conversion efficiency η of S nanoparticles;

[0026] Figure 6 The Cu prepared by the Ce / Cu reaction ratio of 5% in the application example 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-x Biocompatibility of S nanoparticles and cell viability graph;

[0027] Figure 7 The Cu prepared by the Ce / Cu reaction ratio of 5% in the application example 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-x Temperature rise curve of S nanoparticles in cells and animal solid tumor models when irradiated by laser. DETAILED DESCRIPTION

[0028] The method of the present invention is further described in detail below with reference to the embodiments. Example

[0029] (1) In a 37°C water bath, weigh 250 mg of albumin and dissolve it in 8 mL of ultrapure water.

[0030] (2) After stirring and dissolving, add 1 mL of 1 M copper chloride solution to the albumin solution in step (1).

[0031] (3) Under stirring, 0, 0.01, 0.015, 0.025, 0.035, and 0.05 mL (representing Ce / Cu reaction ratios of 0, 1%, 1.5%, 2.5%, 3.5%, and 5%, respectively) of 1 M cerium chloride solution were added to the mixed solution of step (2).

[0032] (4) While stirring, quickly add 0.5 mL of 40 mg / mL sodium hydroxide solution to the mixed solution of step (3), and stir for 3 min.

[0033] (5) While stirring, quickly add 0.4 mL of 39 mg / mL sodium sulfide aqueous solution to the mixed solution of step (4), and stir to react for 2 h.

[0034] (6) After stirring, the sample was first transferred to a dialysis bag (MWCO = 14000 Da) and dialyzed for 12 hours to remove unreacted ions. The agglomerates that may have formed were further removed by low-speed centrifugation at a speed of 5000 rpm for 15 min. The supernatant was collected to obtain a series of ultra-small Cu prepared with different Ce / Cu reaction ratios. 2-x S nanoparticles solution.

[0035] Figure 1 The Ce / Cu reaction ratio is 0, that is, the ultra-small Cu is prepared without adding cerium chloride solution. 2-x Transmission electron microscopy image of S nanoparticles shows that the nanoparticles are uniform in size, about 2~3nm.

[0036] Figure 2 It is a series of ultra-small Cu prepared by different Ce / Cu reaction ratios. 2-x The hydration kinetics of S nanoparticles shows that the introduction of Ce during the reaction does not affect the size distribution of ultra-small Cu 2-x The particle size of S nanoparticles is small, and they show good dispersibility and no agglomeration in aqueous solution.

[0037] Figure 3 It is a series of ultra-small Cu prepared by different Ce / Cu reaction ratios. 2-x The plasma resonance absorption diagram of S nanoparticles shows that the prepared nanoparticles have a strong characteristic absorption peak in the wavelength range of 1100nm~1300nm, which is due to the Cu 2-x The plasmon resonance absorption effect of S further confirmed that Cu 2-x S nanoparticles were successfully synthesized. In addition, as the Ce / Cu reaction ratio increased, Cu 2-x The plasma resonance absorption peak of S continuously blue-shifts, and the corresponding absorption intensity also increases, indicating that only a single factor, Ce, controls the reaction process. 3+ The amount of Cu ions can be adjusted 2-x The number of copper vacancies in S causes the electronic structure of the material to change, that is, the free carrier concentration changes, thereby regulating its plasma resonance absorption characteristics.

[0038] Figure 5 It is Cu prepared by Ce / Cu reaction ratio of 5%. 2-x S and pure Cu 2-x The photothermal conversion efficiency η of S nanoparticles is calculated based on the heating and cooling curves under the same NIR-II 1064 nm laser irradiation. The results show that the Cu prepared with a Ce / Cu reaction ratio of 5% 2-x The photothermal conversion efficiency of S is η = 61.1%, compared with pure Cu 2-x The photothermal conversion efficiency of S nanoparticles is η = 25.6%, which is 2.3 times higher. 3+ The introduction of ions successfully regulated the 2-x The plasma resonance optical absorption of S nanoparticles improves the efficiency of light energy utilization, demonstrating the important value of this preparation technology research.

[0039] The creativity of this patent is further described in detail below in conjunction with comparative examples.

[0040] The comparative example is different from the example in that: in step (2), the mixed solution is added with 0, 0.01, 0.015, 0.025, 0.035, and 0.05 mL (represented as Gd / Cu reaction ratios of 0, 1%, 1.5%, 2.5%, 3.5%, and 5%, respectively) of a gadolinium chloride solution with a concentration of 1 M.

[0041] Figure 4 It is a series of Gd / Cu with different reaction ratios to prepare ultra-small Cu 2-x The plasma resonance absorption diagram of S nanoparticles shows that as the Gd / Cu reaction ratio increases, Cu 2-x The plasma resonance absorption peak position of S did not change significantly, indicating that Gd 3+ The lack of the ability to regulate its plasma resonance absorption characteristics further highlights the innovativeness of the present invention.

[0042] The application advantages of this patent are further described in detail below in combination with application examples.

[0043] The application example is to demonstrate that Cu synthesized by any of the above methods 2-x S nanoparticles can be safely used in the biological field, and the photothermal effects inside and outside the body are used as examples to demonstrate their application potential in the field of photothermal therapy.

[0044] The Cu prepared by the Ce / Cu reaction ratio of 5% in the embodiment 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-xS nanoparticles were mixed with sterile water to prepare aqueous solutions with different copper concentrations (including: 0μg / L without material, 2.5μg / L, 5μg / L, 10μg / L, 20μg / L), and then the above solutions with different concentrations were incubated with mouse breast cancer 4T1 cells in a humidified incubator containing 5% CO2 at 37°C for 12 hours. The cell survival rate of different groups was tested using the CCK8 kit.

[0045] Figure 6 The Cu prepared by the Ce / Cu reaction ratio of 5% in the application example 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-x The biocompatibility cell survival rate diagram of S nanoparticles shows that the survival rate of each group of cells is above 85%, proving that the material has no obvious cytotoxicity.

[0046] The Cu prepared by the Ce / Cu reaction ratio of 5% in the embodiment 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-x The S nanoparticles were mixed with sterile water to prepare an aqueous solution with a copper concentration of 60 μg / L. The above solution was then incubated with mouse breast cancer 4T1 cells. After incubation for 2 to 4 hours, the cells were exposed to NIR-II with a wavelength of 1064 nm and a power of 1 W / cm 2 The Cu prepared by the Ce / Cu reaction ratio of 5% in the embodiment 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-x The S nanoparticles were mixed with sterile water to prepare an aqueous solution with a copper concentration of 150 μg / L. The solution was then injected into mice with breast cancer modeled subcutaneously by 4T1 cells through intratumoral injection. The tumor sites of the mice were exposed to NIR-II with a wavelength of 1064 nm and a power of 1 W / cm 2 The laser was used for 5 min.

[0047] Figure 7 The Cu prepared by the Ce / Cu reaction ratio of 5% in the application example 2-x Pure Cu prepared by reaction of S with Ce / Cu ratio of 0% 2-x When S nanoparticles are irradiated by laser, they Figure 7 a) and animal solid tumor models ( Figure 7 The results show that the Cu prepared in the example has a good thermal stability, no matter for 4T1 cells in vitro or for solid tumors modeled by 4T1 cells in vivo. 2-x S nanoparticles have significant photothermal conversion capabilities, and the Cu prepared with a Ce / Cu reaction ratio of 5% 2-xS nanoparticles showed a stronger photothermal heating effect, demonstrating their superior photothermal therapeutic potential for tumors.

Claims

1. A Cu with continuously adjustable plasmon resonance absorption 2-x S nanoparticle preparation method, characterized in that, The preparation method comprises the following steps: (1) In a low-temperature water bath, the albumin was stirred and dissolved in ultrapure water to prepare a protein aqueous solution with a concentration of 20-40 mg / mL; (2) adding a copper chloride solution to the protein aqueous solution obtained in step (1) and continuing stirring to obtain a protein ligand-ion complex system; (3) adding an auxiliary cationic solution to the protein ligand-ion complex system of step (2) and continuing to stir until a stable mixed solution is formed, wherein the auxiliary cationic solution is a cerium chloride solution, and the molar ratio of cerium chloride to copper chloride is 0.01-0.05:1; (4) Add sodium hydroxide solution to the mixed solution of step (3) and continue stirring to form ions -ligand complex solution, sodium hydroxide solution concentration is 40-60 mg / mL, the mass ratio of sodium hydroxide to albumin is 0.08-0.1:1; stirring reaction time is 3-5 min; (5) Adding sodium sulfide solution to the ion-ligand complex solution of step (4) and continuing stirring, after the reaction is completed, post-treatment is performed to obtain a water-soluble Cu2-xS nanoparticle product.

2. The Cu with continuously adjustable plasma resonance absorption according to claim 1 2-x S nanoparticle preparation method, characterized in that: In step (1), the low-temperature water bath is 37°C and the resistivity of ultrapure water is 18.3 MΩ•cm.

3. The Cu with continuously adjustable plasma resonance absorption according to claim 1 2-x S nanoparticle preparation method, characterized in that: In step (2), the mass ratio of copper chloride to albumin is 0.05-0.08:

1.

4. The Cu with continuously adjustable plasma resonance absorption according to claim 1 2-x S nanoparticle preparation method, characterized in that: In step (5), the concentration of the sodium sulfide solution is 30-60 mg / mL, the molar ratio of copper chloride to sodium sulfide is 1:2, and the stirring reaction time is 2 h.

5. The Cu with continuously adjustable plasma resonance absorption according to claim 1 2-x S nanoparticle preparation method, characterized in that: The post-treatment in step (5) is as follows: first, dialysis is used to remove unreacted ions, and then low-speed centrifugation is used to remove possible aggregates. The centrifugation speed is 5000-6000 rpm, and the centrifugation time is not less than 5 min. The supernatant is collected to obtain the ultra-small Cu 2-x S solution of nanoparticles.

6. Cu obtained by the preparation method according to any one of claims 1 to 5 2-x S nanoparticles.

7. The Cu according to claim 6 2-x S nanoparticles, characterized in that The Cu 2-x The size of S nanoparticles is 2~3nn.

8. The Cu according to claim 6 2-x S nanoparticles, characterized in that The Cu 2-x The plasmon resonance absorption of S nanoparticles is continuously tunable in the second near-infrared region of 1000-1350 nm.

Citation Information

Patent Citations

  • Preparation method of copper sulfide nano material

    CN101559971A

  • Copper sulfide superstructure and its application in improving near infrared thermal conversion efficiency

    CN102219251A